Clinical significance and prognostic role of tumor-associated macrophages infiltration according to histologic location in canine mammary carcinomas. (March 2021) - Monteiro, Lidianne Narducci; dos Reis, Diego Carlos; Salgado, Breno Souza; Cassali, Geovanni Dantas
Abstract: Tumor-associated macrophages (TAMs) have been involved in growth and metastases of human and canine mammary tumors. However, the prognostic importance of TAM specific location in canine mammary tumors (CMT) was not evaluated. In this study, we evaluated the potential role of TAMs in specific histologic locations – intratumoral (iTAM) and stromal (sTAM), as well as total macrophage (tTAM) counts – as prognostic indicators in CMT. Clinicopathologic data from 66 animals with mammary carcinoma and their tumors were used in this study. Samples were stained with anti-macrophage antibody for subsequent TAM count. High levels of iTAM, sTAM, and tTAM were related with advanced clinical stage and vascular invasion. Additionally, tTAM revealed a relation with larger tumor size, while high levels of sTAM and tTAM were also correlated with node metastasis and a poor prognosis based on survival analysis. CMT with aggressive features can reveal higher TAM counts. TAMs are associated with vascular invasion and nodal metastasis, and sTAM and tTAM counts are correlated with overall survival, suggesting they could be used as prognostic indicators in canine mammary carcinomas. Highlights: We evaluated the prognostic importance of tumor-associated macrophages (TAMs) specific location (intratumoral vs. stromal vs. total) in canine mammary tumors. Our data suggested that TAM counts could be used as prognostic indicators in canine mammary invasive carcinomas based on their particular location Canine mammary tumors with aggressive features can reveal higher TAM counts.